2014
DOI: 10.1002/2013wr014664
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Global Width Database for Large Rivers

Abstract: River width is a fundamental parameter of river hydrodynamic simulations, but no global‐scale river width database based on observed water bodies has yet been developed. Here we present a new algorithm that automatically calculates river width from satellite‐based water masks and flow direction maps. The Global Width Database for Large Rivers (GWD‐LR) is developed by applying the algorithm to the SRTM Water Body Database and the HydroSHEDS flow direction map. Both bank‐to‐bank river width and effective river w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
187
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 223 publications
(197 citation statements)
references
References 33 publications
(78 reference statements)
1
187
0
1
Order By: Relevance
“…In this study, we modified the HyMAP-based river width with the Global Width Database for Large Rivers (GWD-LR) (Yamazaki et al, 2014). GWD-LR calculates effective bank-to-bank river width using the SRTM Water Body Database and the HydroSHEDS flow direction map (Lehner et al, 2008).…”
Section: River Routing Schemementioning
confidence: 99%
“…In this study, we modified the HyMAP-based river width with the Global Width Database for Large Rivers (GWD-LR) (Yamazaki et al, 2014). GWD-LR calculates effective bank-to-bank river width using the SRTM Water Body Database and the HydroSHEDS flow direction map (Lehner et al, 2008).…”
Section: River Routing Schemementioning
confidence: 99%
“…Finally, these parameters are defined as constant in time, which is a significant assumption, especially in a region with a marked seasonal climate variability such as the Niger Basin. Remote sensing opens the possibility of estimating the river width by direct measurements and the critical bank-full height by indirect algorithms (Pavelski and Smith, 2008;Yamazaki et al, 2014;Durand et al, 2008). However, the Manning coefficient will still be difficult to estimate even using remote sensing.…”
Section: Trip Specific Parametersmentioning
confidence: 99%
“…However, such relationships might not give the best results locally (for a particular basin). Studies showed that empirical equation does not work well even within one basin and significant errors can be found at subbasin or reach scales (e.g., Miller et al, 2014;Yamazaki et al, 2014). These relationships thus lead to nonnegligible errors which could be reduced using satellite data.…”
Section: Introductionmentioning
confidence: 99%
“…the CC values are 0.99 and 1.0). The old RRS only represents well the area of the Rhône (1), the Ebro (2) and the Maritsa River (5). While the errors are high for other rivers such as the Po (3), the Chelif (4), the Ceyhan River (7).…”
mentioning
confidence: 99%
“…In order to calculate the flow velocity, river width could be classically obtained using geomorphological relationships with annual mean river discharge (e.g. Leopold and Maddock, 1953), but it is also directly available based on remote-sensing (Yamazaki et al, 2014;Allen and Pavelsky, 2015). Above all, this study focuses on small river basins in complex topography as those flowing into the Mediterranean basin and there is a need to verify these results at the global scale and on larger basins.…”
mentioning
confidence: 99%